2022
DOI: 10.1101/2022.09.21.22280205
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive analysis of immune responses in CLL patients after heterologous COVID-19 vaccination

Abstract: Patients with chronic lymphocytic leukemia (CLL) treated with B-cell pathway inhibitors and anti-CD20 antibodies exhibit low humoral response rate (RR) following SARS-CoV-2 vaccination. To investigate the relationship between the initial transcriptional response to vaccination with ensuing B and T cell immune responses, we performed a comprehensive immune transcriptome analysis flanked by antibody and T cell assays in peripheral blood prospectively collected from 15 CLL/SLL patients vaccinated with heterologou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…In total, 60 studies were included for data analysis on booster COVID-19 vaccination, 43 studies reported on the immune response of a total of 4754 patients with a diagnosis of hematological malignancy, and 22 studies determined immune seroconversion in 2440 patients with solid tumors [ 78 , 79 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 60 studies were included for data analysis on booster COVID-19 vaccination, 43 studies reported on the immune response of a total of 4754 patients with a diagnosis of hematological malignancy, and 22 studies determined immune seroconversion in 2440 patients with solid tumors [ 78 , 79 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 ,…”
Section: Resultsmentioning
confidence: 99%
“… Pooled EffectSize (ES) for the immune seroconversion rates of patients with hematological malignancies after the third dose of COVID-19 vaccine [ 28 , 74 , 85 , 87 , 88 , 89 , 91 , 92 , 93 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 104 , 105 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 114 , 116 , 117 , 118 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 134 , 135 ]. …”
Section: Figurementioning
confidence: 99%